2022
DOI: 10.1097/mao.0000000000003457
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Hearing Outcomes in Irradiated and Conservatively Managed Vestibular Schwannoma

Abstract: Objective: Compare hearing outcome for vestibular schwannoma patients following stereotactic radiosurgery (SRS) or conservative management. Study Design: Retrospective review. Setting: University Hospital. Patients: Patients with small-or medium-sized sporadic vestibular schwannoma (intracanalicular or with CPA component <2 cm) who were managed conservatively or underwent SRS with available clinical, radiological, and audiometric data from the time of presentation (or just before radiotherapy for the SRS group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(52 reference statements)
1
8
0
Order By: Relevance
“…Agreeing with our results of superiority of W&S for this subset of patients, a very recent study [Ismail et al, 2022] comparing hearing outcomes of W&S and SRS concluded that patients with small-and medium-sized tumors will have a better hearing outcome if managed via an initial conservative approach with radiotherapy reserved for those demonstrating disease progression.…”
Section: Fn Functionsupporting
confidence: 63%
“…Agreeing with our results of superiority of W&S for this subset of patients, a very recent study [Ismail et al, 2022] comparing hearing outcomes of W&S and SRS concluded that patients with small-and medium-sized tumors will have a better hearing outcome if managed via an initial conservative approach with radiotherapy reserved for those demonstrating disease progression.…”
Section: Fn Functionsupporting
confidence: 63%
“…Comparative studies on the three viable management options for small VS, namely observation, radiosurgery and microsurgery, have shown similar results in terms of tumor control and FN function preservation. As far as hearing function is concerned, while it is generally agreed upon that short-term hearing preservation in small VS is better in patients undergoing a conservative management than in patients subjected to active treatment, whether it is surgery or stereotactic radiotherapy [ 25 , 26 ], data on long- term hearing preservation are more debatable, with some studies showing that hearing function decline is faster in the observation group after the first 2 years of follow up, while it predictably remains stable over time after surgery, as measured at 10 and 15 years [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vestibular schwannomas (VS) are benign tumors growing from the Schwann cells of the vestibular nerve, accounting for 6 to 8% of all intracranial tumors [ 1 ]. Incidence rates were reported to have increased over the years due to the enhancement of clinical awareness and imaging standards, and more intracanalicular VS have been detected.…”
Section: Introductionmentioning
confidence: 99%
“…These patients usually present with unilateral hearing loss or other otological symptoms (unilateral tinnitus, vertigo) while neurological symptoms tend to manifest in cases with larger tumors [ 1 ].…”
Section: Introductionmentioning
confidence: 99%